PENGARUH PEMBIAYAAN MURABAHAH PERIODE 2006:1 – 2013:4 - Mustika Ananda Putri; Trikunawangsih (Media Ekonomi, 2014)
This research examines the effect of variables consisting of Third Party Fund, Non Performing Financing, Inflation, Islamic Certificate of Bank Indonesia  against Murabahah on Islamic Banking in Indonesia. This study uses secondary data regularly (time series data) with the selected time period is the quarter in the period 2006-2013. The required data from Bank Indonesia. The methodology used in this study is multiple regressionClassic OLS. Based on the classic assumption test, a variable that is used to qualify Classical assumption test. Neither Heteroskedasticity Test, Multicollinearity Test and Normality Test. Results of testing the hypothesis by using one sample t-test and paired samples t-test proved that there is variables that influence positively, namely DPK, NPF, and inflation. The SBIS positive effect but not significant.